Dermatofibrosarcoma protuberans: case series and literature review at the rivers state university teaching hospital, port Harcourt, Nigeria - Wakama, Itekena E.; Ijah, Rex Friday Ogoronte A.; Iroegbu-Emeruem, Linda U.; Nkadam, Monday N.; Green, Ibifuro A. (International Surgery Journal, 2025)
Dermatofibrosarcoma protuberans, first described by Jean Darier and Marcel Ferrand in 1924, can affect various body regions, including the head and neck, trunk and limbs. This case series aimed to document the occurrence of this rare dermatofibrosarcoma protuberans as seen at the Rivers State University Teaching Hospital and the neighbouring referring private clinics over five years (2019-2024). The clinical case notes of patients with dermatofibrosarcoma protuberans were retrieved and data were collected and analysed for the study. Eight dermatofibrosarcoma protuberans cases were observed in the study period. The average age of the patients was 43.9 years, with five females and three males. Most of the patients presented with large, locally advanced, ulcerated masses. All but one underwent wide local excision with a minimum excision margin of 3 cm, followed by chemotherapy. A few dermatofibrosarcoma protuberans were recorded at our centre within the period under study. Wide local excision and adjuvant chemotherapy were offered and adjuvant radiotherapy was recommended but not done.